Time-series modelling for forecasting vehicular traffic flow in Dublin - O'MAHONY, MARGARET; GHOSH, BIDISHA; BASU, BISWAJIT (My University, 2005)
The traffic flow at an arterial intersection in a congested urban transportation network in the city of Dublin is modelled in this paper. Three different time-series models, viz. random walk model, Holt-Winters? exponential smoothing technique and seasonal ARIMA model are used for modeling of traffic flow in Dublin. Simulation and short-term forecasting of univariate traffic flow data are done using these models. The data used for modeling are obtained from loop-detectors at a certain junction in the city center of Dublin. Seasonal ARIMA and Holt-Winters? exponential smoothing technique give highly competitive forecasts and match considerably well with the observed traffic flow data during rush hours.
84th Transportation Research Board Conference, National Academies
PUBLISHED
Washington D.C.
Keywords: urban transport network; public transport network; random walk model; Holt-Winters? exponential smoothing technique; seasonal ARIMA model; traffic flow - Dublin; traffic forecasting